Economic uncertainty, parental selection, and the criminal activity of the 'Children of the Wall' - Arnaud Chevalier; Olivier Marie (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
We study the link between parental selection and children criminality in a new context. After the fall of the Berlin Wall, East Germany experienced an unprecedented temporary drop in fertility driven by economic uncertainty. We exploit this natural experiment to estimate that the children from these (smaller) cohorts are 40 percent more likely to commit crimes. We show that women who gave birth at this period were negatively selected. Investigation of the underlying mechanisms reveals that emotional attachment and risk attitudes play important roles in the fertility-crime relationship. Finally, results for siblings support a causal interpretation of our findings.
Keywords: J13; K42; 330; crime; parental selection; fertility; economic uncertainty; risk attitude